KAPABILITAS DINAMIS KELOMPOK TANI BARAMEJI DI KELURAHAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA - Ruth T. Mantiri; Grace A.J. Rumagit; Leonardus R. Rengkung; Yolanda P.I. Rori (Universitas Sam Ratulangi, 2014)
ABSTRACTRuth Trifosa Mantiri. Dynamic Capabilities of Farmers Group Barameji In Kakaskasen 2 Village, North Tomohon sub District. Under guidance of Grace A. J. Rumagit a chairman, Leonardus R. Rengkung and Yolanda P. I. Rori as members.The objective of research is to analyze the dynamic capabilities based on the elements of adaptive, absorptive, innovative, and networking as forming factors of Barameji Farmer’s Group, and to know the efforts made in using and increasing those four elements to build a group to be able to conduct a sustainable development and can win the market competition.This research was conducted from February until May 2014, started from preparation until report compilation. The data used in the form of primary data and secondary data. This research was carried out with saturation sampling technique, in which include all members of a population of 14 people. Data analysis was done descriptively using a Likert scale and followed by t-test.The results showed that those element of adaptive, absorptive, innovative, and networking are strong elements as a forming factor in the dynamic capabilities of Barameji Farmer’s Group. Adaptive capability was used to identify natural phenomena and build green house, and the use of dolomite. As the effort in increasing adaptive capability, the approach and deepening characteristics of partner and competitors, as well as green house renovation could be conducted. Absorptive capability be used in the evaluation of implemented activities and strategies of other farmers. Increasing of absorptive capability was conducted by expanding the network and more intense of searching information.The use of innovative capability was conducted through the discovery of some innovation process, whereas its increase sought by strengthening absorptive continuous. The networking capability used in cooperation, then improved by expanding the partnership and develop a seed distribution system.